2017
DOI: 10.1159/000485945
|View full text |Cite
|
Sign up to set email alerts
|

SC1 Promotes MiR124-3p Expression to Maintain the Self-Renewal of Mouse Embryonic Stem Cells by Inhibiting the MEK/ERK Pathway

Abstract: Background/Aims: Self-renewal is one of the most important features of embryonic stem (ES) cells. SC1 is a small molecule modulator that effectively maintains the self-renewal of mouse ES cells in the absence of leukemia inhibitory factor (LIF), serum and feeder cells. However, the mechanism by which SC1 maintains the undifferentiated state of mouse ES cells remains unclear. Methods: In this study, microarray and small RNA deep-sequencing experiments were performed on mouse ES cells treated with or without SC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…To reveal whether the alteration of mtDNA 5hmC contributes to brain injury after cerebral I/R injury, we administered SC1 (pluripotin, an inhibitor of Tet2 expression) to mice via an intracerebroventricular injection. Maybe SC1 has other functions, such as inhibit the kinase enzymes in embryonic stem (ES) cell self‐renewal and cancer formation (Wei et al, ), but its main function is to inhibit the expression of Tet enzyme. Quantitative PCR showed that Tet2 mRNA level was decreased by SC1 treatment after I/R injury (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reveal whether the alteration of mtDNA 5hmC contributes to brain injury after cerebral I/R injury, we administered SC1 (pluripotin, an inhibitor of Tet2 expression) to mice via an intracerebroventricular injection. Maybe SC1 has other functions, such as inhibit the kinase enzymes in embryonic stem (ES) cell self‐renewal and cancer formation (Wei et al, ), but its main function is to inhibit the expression of Tet enzyme. Quantitative PCR showed that Tet2 mRNA level was decreased by SC1 treatment after I/R injury (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, mitochondrial dysfunction has been well characterized as a precursor to cell death after ischemic injury (Yang et al, ). Neuronal damage after cerebral ischemia is selective and mostly affects vulnerable regions of the brain, such as the hippocampus (Park et al, 2017; Zhang, Wei et al, ). Mitochondrial dysfunction is considered one of the critical determining factors relevant to the selectivity of ischemic brain injury (Ruiz, Matute, & Alberdi, ), and several mechanisms are thought to be responsible for the delayed mitochondrial failure observed after ischemia/reperfusion injury (Andalib et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that about one-third of the human genome may be regulated by miRNAs through complicated mechanisms (Friedman, Farh, Burge, & Bartel, 2009). It has been proved that miRNAs play an important part in many physiological or pathophysiological processes of the body, containing differentiation, development, apoptosis, metabolism and proliferation (Sliwinska, Kasinska, & Drzewoski, 2017;Tao, Shen, Luo, Xu, & Liang, 2017;Wei et al, 2017;Zhang, & Xu, 2016). Accumulated evidence have shown that miRNA could modulate cardiomyocyte differentiation from ESCs and promote the process of myocardial cell renewal after myocardial ischemic necrosis (Luo et al, 2017;White, Pang, & Yang, 2016;Zhu, Liu, Lai, Li, & Wang, 2016).…”
Section: Introductionmentioning
confidence: 99%